Is Isolated Hip Strengthening or Traditional Knee-Based Strengthening More Effective in Patients With Patellofemoral Pain Syndrome? A Systematic Review With Meta-analysis. Issue 7 (28th July 2021) - Na, Yuyan; Han, Changxu; Shi, Yuting; Zhu, Yong; Ren, Yizhong; Liu, Wanlin
Background: Focus on the importance of hip muscle strength in patients with patellofemoral pain syndrome (PFPS) has recently increased. It is unknown whether patients with PFPS will benefit more from hip strengthening compared with traditional knee-based strengthening. Purpose: To compare the efficiency of isolated hip strengthening versus traditional knee-based strengthening for patients with PFPS. Study Design: Systematic review; Level of evidence, 2. Methods: We conducted a search for studies comparing isolated hip strengthening and knee-based strengthening by using the MEDLINE, Embase, and Cochrane Library electronic databases. The methodological quality of included studies was assessed using the PEDro scale. Predetermined variables from each study were extracted and analyzed. Results: A total of 5 comparative studies were included in this review; all studies were of moderate to high quality and reflected good internal and external validity. Pain (visual analog scale [VAS]) and function (Anterior Knee Pain Scale) scores improved in both the hip and knee groups after strengthening intervention, although no statistically significant differences were seen between groups in the pooled analysis. In 2 studies, VAS pain scores were reduced earlier for patients in the hip group than for those in the knee group ( P < .05). In 1 study, improvement in Western Ontario and McMaster Universities Osteoarthritis Index function scores in the hip group was statistically superior compared with those in the knee group after intervention and at 6-month follow-up ( P < .05). In 2 studies, patients in the hip group exhibited statistically greater hip abductor and extensor strength than did those in the knee group after intervention ( P < .05). Conclusion: The best-available evidence suggests that overall, isolated hip strengthening and knee strengthening were equivalent for treatment of PFPS.